Population dynamics of Clibanarius antillensis (Crustacea: Anomura: Diogenidae) of the location of Puerto Abajo, New Sparta state. during the march-september 2014 period - Contreras Mata, Orgelis (2020)
On the Venezuelan coast, the genus Clibanarius is represented by four species, of which there is an almost absolute ignorance about the ecology of C. antillensis. For this reason it was proposed to carry out this research whose main objective was to study its population dynamics in the town of Puerto Abajo. Fortnightly samples were sampled during the March-September 2014 period. The sample consisted of 1098 specimens: 556 (50,64%) females (♀), of which 335 were ovigerous and 542 (49,36%) males (♂) The sexual ratio was 1♀: 1♂. The lowest number of organisms was collected in the month of March and the largest in May and August. The t-student of the wet weight (t = 1,66; p> 0,05) shows that there are no affected differences between females and males, while the wet weight relationship with the shield length shows a negative allometric growth. The population parameters for ♂ and ♂ of the hermit were, respectively: asymptotic length L∞ = 7,40 mm and 7,90 mm; growth coefficient: k = 0,20 / year-1 and 0,22 / year-1 ; the theoretical age: t0 = -0,22 / years-1 and -0,2 / years-1 ; calculated age limit: A0,95 = 13,8 years and 12,5 years. The coefficient of variation obtained for both ♀ (CV = 22,49%) and ♂ (CV = 27,75%), modified that the pattern of growth in length of the species differs statistically in relation to sex.